Implementation and Obstacles in The Execution of Warranties as Object of Liability Credit Rights in PT BPR Gunung Rizki Pusaka Utama Semarang - Eliza Chandradewi Arius; Rya Rizqi Amalia; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Indonesia's economy is growing by leaps and bounds, where banking is very supportive financing of economic activities in order to meet the needs of Indonesian society. Each implementation agreement on bank credit, is always associated with the presence of collateral, the collateral which was born in the credit agreement is already an agreement between the parties to bind themselves to each other. Granting Mortgage is very important in the credit agreement for the lender has the right to the sale of goods as collateral. Aims to identify and analyze the execution of objects Mortgage as loan collateral at PT BPR Gunung Rizki Pusaka Utama Semarang and analyze the barriers that occur and solutions in the travel in overcoming these obstacles. The method used is the method of normative legal approach.Execution of objects Mortgage as loan collateral at PT BPR Gunung Rizki Pusaka Utama Semarang do with Parate Execution. Where the execution of Encumbrance using Parate Execution aims to obtain repayment of its receivables efficiently and quickly. Barriers that occur in the implementation of the Mortgage object is the object of a third party guarantee, the collateral has not been registered, and the lack of good faith of the debtor.Keywords: Execution; Mortgage; Security; Credit.